Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor. (1st January 2023) - Younas, Muhammad; Shafique, Sumeer; Faisal, Abrar; Hafeez, Ainy; Javed, Fahed; Mustafa, Maria; Rehman, Fahad
Graphical abstract: Highlights: Microplasmas can reduce energy requirements of water plasmolysis on par with electrolysis. Hydrogen producing technologies could produce maximum 25-30 g/kWh energy yield. The optimized packed bed microplasma reactor in current study produces 23.9 g/kWh energy yield. Microplasma reactor produces 16.31% more hydrogen energy yield in comparison to electrolysis. Microplasma reactor can be used for decentralized power system for rural areas. Abstract: Hydrogen as secondary energy carrier is one of the promising routes to meet renewable and sustainable energy demand. Hydrogen production using water plasmolysis, so far, has been considered as energy intensive. However, recent developments in the field of microplasmas has reduced energy requirement of water plasmolysis on par with electrolysis. However, there's still room for improvement as water vapors dissociation efficiencies are less than thermodynamic and kinetic limits. One of the ways to do that is to split microchannel in plasma into sub-micron channels by packing beads inside the reactor. The current study investigates the plasmolysis of water vapours (steam) and argon gas with (1) empty channel plasma reactor and (2) glass beads packed plasma reactor. A custom-made Corona-DBD hybrid microplasma reactor has been designed and employed for water steam plasmolysis. This study aims to investigate the feasibility of water vapors dissociating into hydrogen at a relatively small interelectrode gap at atmospheric pressure. The minimum breakdown voltage has been found to be 3.7 kVpk-pk at 5 mA current. The maximum hydrogen production rate was observed 23.9 g/kWh at optimized conditions for the glass beads packed plasma reactor. So, in current study glass beads packed plasma microreactor yielded 23.9g of H2 /kWh which is significantly higher than any previously published study